THE ROLE OF WORK MOTIVATION IN MEDIATING COMPENSATION AND TRANSFORMATIONAL LEADERSHIP ON TEACHER PERFORMANCE AT AL BAITUL AMIEN EDUCATIONAL INSTITUTION, JEMBER - Tamriatin Hidayah; Hary Sulaksono (ABM: International Journal of Administration, Business and Management, 2023)
This study aims to determine the effect of compensation and transformational leadership on teacher performance through motivation as an intervening variable at the Al Baitul Amien Education Institute, Jember. The population in this study were all teachers at the Al Baitul Amien educational institution, while the sample was taken by proportional sampling. The analytical method used is path analysis (Path Analysis) and also the Sobel test to see the role of the motivational variable as an intervening variable. The results of the study show that there is a direct effect of compensation and transformational leadership on teacher work motivation and performance. Work motivation affects performance.